2014
DOI: 10.1007/s10886-014-0518-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Pathogen Candidatus Liberibacter Solanacearum on Tomato Host Plant Volatiles and Psyllid Vector Settlement

Abstract: Candidatus Liberibacter solanacearum (CLso) is an unculturable bacterium vectored by the tomato potato psyllid (TPP) Bactericera cockerelli and has been associated with Zebra chip disease in potato and with other economically relevant symptoms observed in solanaceous crops. By altering their host and vector's biological system, pathogens are able to induce changes that benefit them by increasing their transmission rate. Understanding these changes can enable better targeting of mechanisms to control pathogen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…Those changes could be advantageous, neutral, or disadvantageous for transmission. It is well‐known that changes in host plants mediated by Lso affect host preference by its vectors, which increases Lso transmission (Davis et al., ; Mas et al., ). Nevertheless, the direct effects of Lso on its vectors have received little attention, and this study proves that Lso may directly modify the stylet penetration activities of its vector, B. trigonica .…”
Section: Discussionmentioning
confidence: 99%
“…Those changes could be advantageous, neutral, or disadvantageous for transmission. It is well‐known that changes in host plants mediated by Lso affect host preference by its vectors, which increases Lso transmission (Davis et al., ; Mas et al., ). Nevertheless, the direct effects of Lso on its vectors have received little attention, and this study proves that Lso may directly modify the stylet penetration activities of its vector, B. trigonica .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in recent years that some phytopathogens manipulate the behavior of their vectors by altering the attractiveness of the vector's host plants by increasing the amount or changing the composition of VOCs emitted by infected plants. This has been shown for pathogenic bacteria (Mayer et al, 2008a,b;Davis et al, 2012;Mann et al, 2012;Shapiro et al, 2012;Mas et al, 2014) and viruses (Eigenbrode et al, 2002;Mauck et al, 2010). Recently it was shown that the apple proliferation phytoplasma Ca.…”
Section: Plant-phytopathogen-vector Interactionsmentioning
confidence: 73%
“…For instance, B. cockerelli initially settled on infected potato plants, but later moved to and oviposited preferentially on plants that had been exposed to uninfected psyllids (Davis et al ., ). Interestingly, CLso‐negative B. cockerelli settled preferentially on CLso‐infected tomato plants, while CLso‐positive psyllids preferred the uninfected tomato plants (Mas et al ., ). Similarly, D. citri were more attracted to the volatile profiles of CLas‐infected sweet orange trees ( Citrus sinensis ) initially; however after feeding, psyllids preferentially dispersed to noninfected rather than infected plants, but the infectious status of the insect did not affect the psyllid behavior (Mann et al ., ).…”
Section: The Effect Of Bacterial Pathogens On Plant Metabolism and Immentioning
confidence: 97%